Fabrication and electrochemical properties of diamond layers grown on tungsten wire by HF CVD method - Torz-Piotrowska, Riwana; Uniszkiewicz, Cezary; Szreiber, Maciej; Wrzyszczyński, Andrzej; Staryga, Elżbieta; Runka, Tomasz; Kasprowicz, Dobrosława (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Un-doped polycrystalline diamond thin films have been grown on tungsten substrates by hot filament chemical vapor deposition (HF CVD) using a hydrogen and methanol vapor mixture. Diamond films have been analyzed by Raman spectroscopy and scanning electron microscopy (SEM). Cyclic voltammetric behavior of diamond films of different quality and morphology has been studied in acetonitryle with (n-Bu)4NClO4 and in 0.1 M KCl aqueous solutions. Preliminary cyclic voltammetry (CV) measurements showed that our electrodes have a wide potential range over which negligible background response current is observed. The potential windows depend on the type of solvent. In the case of water solution the decomposition of water occurs electrochemically and evolves O2 during positive (anodic) polarization and H2 evolution during negative (cathodic) polarization. The electrochemical properties of diamond electrodes have been evaluated by performing cyclic voltammetry measurements in [Fe(CN)6]3–/4– with 0.1 M KCl. The electrode demonstrates reversible kinetics during electrochemical analysis.
Optica Applicata, Vol. 39, 2009, nr 4, s. 951-957
Keywords: optyka; CVD diamond; diamond; cyclic voltammetry; Raman spectroscopy; scanning electron microscopy (SEM)